Enrollment Intention and Willingness to Pay in Business Schools: Using the Stimulus–Organism–Response (S-O-R) Framework - Liza Agustina Maureen Nelloh; Leonnard Ong; Oliandes Sondakh (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Business schools in Indonesia are experiencing a declining trend in student enrollment. Prior studies in this area have predominantly focused on candidates’ willingness to pay, with limited attention to the underlying psychological and branding mechanisms that shape students’ enrollment decisions and willingness to pay (financial commitment).Purpose: This study aims to examine the applicability of the Stimulus–Organism–Response (S-O-R) model in the context of Indonesian business schools by analyzing how institutional stimuli, namely facilities, study programs, tuition fees, opinions, and digital marketing promotion, influence campus branding, enrollment intention, and willingness to pay.Design/methodology/approach: The study employs a quantitative approach using purposive sampling to collect data from 126 prospective business school students across several cities in Indonesia. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM), including both outer model and inner model analyses, to examine the relationships proposed in the S–O–R framework.Findings/Result: This study found partial support for the proposed S–O–R model. Several institutional attributes facilities, study programs, tuition fees, opinions, and digital marketing promotion are positively influence campus branding, although most of these relationships show relatively small effect sizes. Among these attributes, only facilities and opinions demonstrate significant direct relationships with students’ intention to enroll. Campus branding shows a strong relationship with enrollment intention and a moderate relationship with willingness to pay. In contrast, digital marketing promotion, study programs, and tuition fees do not demonstrate significant direct effects on enrollment intention. In addition, the relationship between enrollment intention and willingness to pay is not statistically significant.Conclusion: This study concludes that prospective students’ responses toward business schools appear to be shaped more by their overall perception of campus branding than by individual institutional attributes. Although several attributes contribute to the formation of campus branding, only facilities and opinions demonstrate direct relationships with enrollment intention. The absence of significant effects from digital marketing promotion, study programs, and tuition fees suggests that these attributes may not independently drive enrollment decisions in this context. In addition, the non-significant relationship between enrollment intention and willingness to pay indicates that financial commitment may involve additional considerations beyond the intention to enroll. This indicates that prospective students rely more on their perceptions of institutional branding when forming financial commitments, rather than on behavioral intention alone.Originality/value (State of the art): This study contributes originality by applying the S-O-R model to business school settings and incorporating willingness to pay as an additional response variable, which is rarely examined in higher education research. While campus branding serves as the dominant organism-level mechanism and clarifies the indirect effects of institutional stimuli, the study offers a more precise explanation of how perceptions of value are formed in emerging market business education. Keywords: campus branding, candidate students, enrolment intention, s-o-r model, willingness to pay